Syndrome of transient headache and neurological deficits with cerebrospinal fluid lymphocytosis mimicking dengue encephalitis in a child - Suresh, Indrajit; Deb, Priyanka; D., Chandra Babu; H.R., Jeevan (International Journal of Research in Medical Sciences, 2017)
The syndrome of transient headache and neurological deficits with cerebrospinal fluid lymphocytosis (HaNDL) has been infrequently reported in children. This condition can mimic many serious conditions of the central nervous system, while actually being benign in nature. The authors present the report of an 8 year old developmentally normal female with family and personal history of migraine, which was initially suspected to have Dengue encephalitis. She had an episode of seizures, meningism and altered sensorium. Normal mental status and physical findings were observed intermittently. Detailed evaluation including analysis of blood, cerebrospinal fluid (CSF) and neuroimaging were done. Neuro-infections, vascular pathology and autoimmune disorders were ruled out prior to reaching a diagnosis of HaNDL. She responded well to symptomatic treatment and made a full recovery. She was discharged on migraine prophylaxis considering her history. Dengue as causation and the occurrence of seizures in HaNDL has not been reported previously.